Risk factors for nonunion of ulnar styloid fractures associated with distal radius fractures - Kaya, Emre; Akdemir, Nurtaç Alper; Geçer, Ali; Konukoğlu, Levent (The European Research Journal, 2025)
Objectives: A major complication of ulnar styloid fractures (USFs) associated with displaced distal radius fractures (DRFs) is nonunion, which can result in pain and instability of the distal radioulnar joint (DRUJ). This study aimed to identify the risk factors influencing the healing of USFs in cases of displaced DRFs, when treated using different methods - either surgically with plate-screw fixation, or conservatively with closed reduction and a plaster cast. Methods: A total of 41 patients with USFs associated with DRFs, treated either surgically or conservatively, were retrospectively evaluated. Fractures were classified based on the treatment modality (surgical/conservative), demographic data, and radiographic characteristics. The Fernandez classification system was used to categorize DRFs. USF displacement was stratified into two groups: displacement >2 mm and 2 mm and nonunion. No significant association was observed between nonunion and other variables, including treatment modality, age, sex, laterality, or fracture classification. Conclusions: The development of nonunion in USFs accompanying DRFs is not significantly influenced by treatment modality, age, sex, fracture classification, or side of involvement. However, a displacement of the USF greater than 2 mm is associated with a significantly increased risk of nonunion.